Investing across Borders 2010 : Indicators of Foreign Direct Investment Regulation in 87 Economies - International Finance Corporation (Washington, DC, 2017)
Investing Across Borders 2010 (IAB) presents cross-country indicators analyzing laws, regulations, and practices affecting foreign direct investment (FDI) in 87 economies. The indicators focus on 4 thematic areas measuring how foreign companies invest across sectors, start local businesses, access industrial land, and arbitrate commercial disputes. The indicators combine analysis of laws and regulations, as well as their implementation. They explore differences across countries to identify good practices, facilitate learning opportunities, stimulate reforms, and provide cross-country data for research and analysis. The project's methodology is based on the World Bank Group's Doing Business initiative. The IAB indicators draw on data collected through a survey of lawyers, other professional service providers (mainly accounting and consulting firms), investment promotion institutions, chambers of commerce, and other expert respondents in each of the countries measured. Between April and December 2009 more than 2,350 experts in 87 economies responded to the survey to provide data for this report. This chapter presents the report's main findings including examples of FDI competitiveness-enhancing practices for each indicator area. It also provides key results for each region. IAB does not measure all aspects of the business environment that matter to investors. For example, it does not measure security, macroeconomic stability, market size and potential, corruption, skill levels, or infrastructure quality. Still, the indicators provide a starting point for governments seeking to improve their competitiveness in attracting foreign investment.